Biosafety in Dental Health Care During the COVID-19 Pandemic: A Longitudinal Study - Miguita, Lucyene; Martins-Chaves, Roberta Rayra; Geddes, Victor Emmanuel Viana; Mendes, Suellen da Rocha; Costa, Sara Ferreira dos Santos; Fonseca, Paula Luize Camargos; Menezes, Diego; Souza, Rafael Marques de; Queiroz, Daniel Costa; Alves, Hugo José; Freitas, Raphaela Alvarenga Braga de; Cruz, Aline Fernanda; et al. (Frontiers in Oral Health, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic had quite an impact on dental health care. Concerns about the risk of SARS-CoV-2 transmission through contaminant fluids and droplet formation during several dental procedures highly impacted dental health care, drastically reducing the number of dental practices worldwide. To monitor SARS-CoV-2 contamination in dental clinics, a longitudinal study was carried out during the return of dental practice at university. Methods Dental health care professionals [(DHCPs); teachers, undergraduate dental students, and dental assistants] and patients were screened for SARS-CoV-2 RNA in a dental school clinic environment from 11th January to 12th March 2021 (9 weeks). Serological testing was performed on DHCPs in two-time points. Additionally, samples with low Ct values were sequenced to identify the circulating SARS-CoV-2 variant and possible transmission clusters. Results We found a low number of dental staff (5.8%), patients (0.9%), and environment sites (0.8%) positive for SARS-CoV-2. Most positive cases had asymptomatic to mild symptoms, and two asymptomatic DHCPs presented prolonged infection. In the first week after previous exposure to COVID-19, 16.2% of DHCPs had IgM or IgG antibodies against SARS-CoV-2, and 1/3 of them had undetected antibodies in the last weeks. The variant zeta (P.2) could be detected. No cross-infection was observed between participants. Conclusion Our study suggests that dental practice can be safely executed when adequate control measures and biosafety protocols are applied. DHCP and patient testing, patient telemonitoring, proper use of personal protection equipment, and sanitization of surfaces are essential to avoid SARS-CoV-2 cross-infection in dental practice.